The first record of an audible sound produced by a ghost moth, Phassus (Hepialidae) from Costa Rica - Sandoval Vargas, Luis Andrés (2015)
Sound production in lepidopteran adults has been reported in at least 13 families. The majority of these families produce ultrasonic sounds that are inaudible to humans. Here we report the first record of an audible sound produced by a Phassus sp. (Hepialidae) from Costa Rica. The sound is clicking or creaking-like, produced as the moth raises its abdomen dorsally (bending the abdomen backwards). The mechanism of this sound production is unknown, but supposed to be a case of stridulation. As the moth raised its abdomen, blue iridescence patches (likely ornamented by structural colors) on the dorsum were observed. The clicking sound is composed of two main parts which varied in frequency and duration. Inferred from the brief observation, the raising of the abdomen and sound production are possibly used for defense against natural enemies.